Evaluation of the relevance of touch imprint cytology in the diagnosis of various neoplastic lesions - Chandrakar, Jayanti; Srivastava, Shruti (International Journal of Research in Medical Sciences, 2017)
Background: Imprint is a very simple and rapid technique for tissue diagnosis. Imprint is a touch preparation in which tissue is touched on a slide and it leaves behind its imprint in the form of cells on the glass slide. In present study we have correlated the cytological diagnosis by imprint with histological diagnosis and tried to evaluate the accuracy and usefulness of this. Methods: The study was conducted in department of Pathology of Pt J.N.M. Medical College, Raipur (C.G) India. From neoplastic lesions imprint smears were prepared immediately after resection of surgical specimen. After preparation of imprint smears specimens were processed by routine histopathological processing. Final reports of both processes were compared to know accuracy of diagnosis by imprint cytology. Results: Out of total 110 cases, 25 cases were benign and 85 cases were malignant. Out of the 25 benign cases, 14 (56%) were diagnosed correctly and correlated with histological diagnosis. while 11 (44%) cases were false negative. No false positive cases were there. Out of 85 malignant lesions 78 (91.76%) were diagnosed correctly and correlated on histopathology, while 7 (8.23%) were false negative. Overall diagnostic accuracy by imprint smear after histological correlation was 83.63% increasing to 91.76% for malignant lesions. Conclusions: With an accuracy rate of 83.63% we can say that imprint cytology is a quick reliable simple and cost effective procedure.